Handbook of Data Compression - Salomon, David; Motta, Giovanni (Springer London : Imprint: Springer, 2010)
"A wonderful treasure chest of information; spanning a wide range of data compression methods, from simple text compression methods to the use of wavelets in image compression. It is unusual for a text on compression to cover the field so completely." - ACM Computing Reviews "Salomon's book is the most complete and up-to-date reference on the subject. The style, rigorous yet easy to read, makes this book the preferred choice ... [and] the encyclopedic nature of the text makes it an obligatory acquisition by our library." - Dr Martin Cohn, Brandeis University Data compression is such an important tool in modern computing that some researchers even suggest that all computing is compression! This comprehensive fifth edition of David Salomon's highly successful reference, Data Compression, now fully reconceived under its new title, Handbook of Data Compression, is thoroughly updated with the latest progress in the field. This all-inclusive and user-friendly reference work discusses the wide range of compression methods for text, graphical data (still images and movies), and audio. Among the important features of this accessible reference are a detailed index and helpful glossary, an extensive bibliography, an appendix presenting and explaining the basic concepts and terms in information theory, liberal use of illustrations and data tables, and broad coverage discussing the use and comparative benefits of different methods. The book's logical, clear and lively presentation is organized around the main branches of data compression, for ease in usage. This meticulously enhanced, reliable handbook is an essential companion for all computer scientists; computer, electrical and signal/image processing engineers; and scientists needing a comprehensive compilation of compression methods. It requires only a minimum of mathematics and is well-suited to nonspecialists and general readers who need to know and use this valuable content. David Salomon is a professor emeritus of computer science at California State University, Northridge. He has authored numerous articles and Springer books, including A Concise Introduction to Data Compression, Variable-length Codes for Data Compression, Transformations and Projections in Computer Graphics, Foundations of Computer Security, Curves and Surfaces for Computer Graphics, Coding for Data and Computer Communications, Data Privacy and Security, Guide to Data Compression Methods, and Computer Graphics and Geometric Modeling. NEW topics and features: Dedicated chapters on basic, advanced, and robust variable-length codes PK (packed) fonts PAQ, an open-source, high-performance compression algorithm and free software Interesting LZ variants, such as LZR, LZB, SLH, LZPP, LZT and LZJ Antidictionary methods The HD photo (a.k.a. JPEG XR) compression method ALPC lossless image compression GS-2D-LZ Encoding Spatial prediction, a combination of JPEG and fractal-based image compression The extension to the H.264/AVC video compression standard for temporal, spatial, and quality scalable video coding The VC-1 video codec Syllable-based compression Stuffit compression software.